Process of soil degradation associated with desertification in the Paraguana Peninsula, Venezuela (Ágora de Heterodoxias, 2017)
Desertification occurs as a result of land degradation in arid and semi-arid zones resulting from various factors, including climatic variations and land use change. Among the processes related to desertification of land we have the following i) salinization; ii) reduction of soil organic matter; and iii) water erosion. These processes were evaluated in the Falcon municipality of the Paraguana Peninsula in order to delimit areas with different levels of desertification. The methodology consisted in the compilation of documentary and field information of each one of the variables related to the mentioned processes. A high proportion of the soils of the municipality presents problems of slight salinity (54% of the territory) and 27% are saline soils. The change in land use generated a significant effect on the reduction of soil organic matter, with the use of melon cultivation leading to higher losses of organic matter, which were between 50-70 % in relatively short times, from 15 to 20 years. Soil erodibility presented moderately high values ​​(greater than 0.03 t.ha.h.MJ-1.ha-1.mm-1), which expresses the susceptibility of the soil to be separated and transported by rain and surface flow
Keywords: Arid zones; soil salinization; land degradation; erosionability; organic matter depletion